Auricular Acupuncture Associated with Reduced Waist Circumference in Overweight Women-A Randomized Controlled Trial. (18th December 2019) - Lillingston, Felicity; Fields, Paul; Waechter, Randall
Abstract : Obesity and subsequent ill health have reached epidemic proportions in developed countries, and many developing countries are on the same trajectory. Weight loss and sustaining a healthy weight have posed a significant challenge for individuals, patients, health-care providers, and public health experts. The literature suggests that dietary advice and lifestyle changes alone have limited sustainable impact for those who are seeking to achieve a healthy weight. Supplementary techniques to control weight, such as acupuncture and auricular acupuncture (AA), have shown mixed results and failed to clearly demonstrate a conclusive impact. This study aimed to provide clarity about the impact of AA on weight loss via a randomized controlled trial. Data were collected from patients to identify measurable girth reduction, weight loss, dietary choices, and mood changes over seven weekly sessions of AA ( n = 30) versus sham needle as control ( n = 28). Results demonstrated a large and highly significant AA treatment effect for reduced waist circumference over the course of the seven-week intervention. While the treatment effect for weight loss and BMI was not significant, this negative result may have been mediated by the relatively short duration of the study. Results also demonstrated a significant mood improvement across participants in both the AA intervention and control group as the intervention progressed. Further studies are required to determine if the reduction in waist circumference is driven specifically by the AA alone or in conjunction with improved mood. The results also have potentially significant implications for healthcare delivery in the fight against overweight and obesity.